Historicizing the ideology of 'the market'. (October 2021) - Eagleton-Pierce, Matthew
The concept of the market is a linchpin notion in the analysis of contemporary capitalism. This article seeks to question how the term has tended to oscillate between two problematic types of use: either underspecifying the history and politics tied to the concept or, conversely, overloading the notion with a proliferation of too many meanings and applications. As a way to chart an alternative approach which can objectify and critique some of these patterns, this paper re-excavates the notion of 'the market' through a historicization of its ideological production and consumption. In particular, the argument brings political economy scholarship into a conversation with theoretical advances in the analysis of ideology, notably Michael Freeden's so-called 'morphological approach'. The article illuminates not only past usage patterns but also how the potency of the expression has been refreshed within recent decades associated with neoliberalism. In this way, through a dissection of this master category, the article also aims to contribute to identifying more precisely what is new in the neoliberal ideological ecosystem.